2009
DOI: 10.1111/j.1708-8240.2009.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Assessing Light Enhancement of In‐office Tooth Whitening

Abstract: Use of light enhancement for in-office whitening leads to immediate color change, after which there was significant color and shade rebound within 7 days as well as moderate-to-severe tooth sensitivity during and after treatment. CLINICAL SIGNIFICANCE Increased tooth sensitivity during treatment and appreciable short-term color rebound after treatment may impact the utility of in-office tooth whitening with peroxide and light as a stand-alone esthetic procedure. (J Esthet Restor Dent 21:336-347, 2009).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 9 publications
6
27
2
Order By: Relevance
“…101 Several studies stated that their digital imaging system is reproducible and reliable in evaluating changes in whiteness of teeth 102 and that clinical measurement of tooth color was highly reproducible with very high intra-class correlations for the image pairs. 53 Using the imaging system tested in reference 53, it was found that: (a) twice-daily use of 6% hydrogen peroxide whitening strips resulted in teeth becoming lighter and less yellow compared to baseline during initial 2-week use 103 ; (b) short-term color rebound after treatment may impact the utility of in-office tooth whitening with peroxide and light as a stand-alone esthetic procedure 104 ; and (c) two professional at-home tooth whitening systems in a teenage population resulted in significant reduction in yellowness and increase in lightness after two weeks of treatment on each arch. No significant difference between groups was recorded.…”
Section: 6mentioning
confidence: 98%
“…101 Several studies stated that their digital imaging system is reproducible and reliable in evaluating changes in whiteness of teeth 102 and that clinical measurement of tooth color was highly reproducible with very high intra-class correlations for the image pairs. 53 Using the imaging system tested in reference 53, it was found that: (a) twice-daily use of 6% hydrogen peroxide whitening strips resulted in teeth becoming lighter and less yellow compared to baseline during initial 2-week use 103 ; (b) short-term color rebound after treatment may impact the utility of in-office tooth whitening with peroxide and light as a stand-alone esthetic procedure 104 ; and (c) two professional at-home tooth whitening systems in a teenage population resulted in significant reduction in yellowness and increase in lightness after two weeks of treatment on each arch. No significant difference between groups was recorded.…”
Section: 6mentioning
confidence: 98%
“…Some studies showed that dehydration during the isolation for bleaching process contributed to immediate post treatment color change 16,18,22,28) and color must be evaluated after water uptake. In this investigation after each bleaching protocol; the teeth were immersed in distilled water and color measurements were done after 1 week for eliminating the effect of tooth dehydration during bleaching procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is corroborated by clinical findings showing that the prevalence and intensity of tooth sensitivity is higher when light is associated with in-office bleaching. [1][2][8][9]12 Under such high inflammation levels, desensitizing agents based on 2% potassium nitrate are likely less effective in reducing the transmission of tooth pain immediately after bleaching.…”
Section: 16mentioning
confidence: 99%
“…[3][4] Clinical studies investigating the use of supplementary light on the effectiveness of vital bleaching have been controversial. [1][2][5][6][7][8][9][10] Even though evidence is not definitive on the use of light-enhanced bleaching, patients often demand its use due to media coverage. Many clinicians look upon light-activated bleaching as important for patient satisfaction and because many current systems use light activation in conjunction with hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation